Women's Silence Imaginative-Proximity in Media - Saudah Saudah; Dodot Sapto Adi (Universitas Merdeka Malang, 2022)
The condition of society is equal to the need for information presented in the mass media. This uniqueness places women in an important position in finding the existence of the media. Women have a dual position as creators and connoisseurs of mass media, because there is sufficient time to utilize the media as a solution. The growing phenomenon lies in the reality that can be formed from the conditions created between women, and conventional mass media as well as renewable media. By conducting in-depth interviews, the results show that the media has the ability to form and strengthen identities, and get closer to the media, so that they can carry out the process of adapting to the patterns presented by the media. This situation causes the emergence of women's closeness to the mass media which is shrouded in a distinctive imagination. Each will mean the information presented, and provide a process of knowing, imitating, and forming identity on the mass media.Keywords: Women, Mass Media, Medium Wise